Formation of unexpected silicon- and disiloxane-bridged multiferrocenyl derivatives bearing Si–O–CHCH2 and Si–(CH2)2C(CH3)3 substituents via cleavage of tetrahydrofuran and trapping of its ring fragments. Issue 35 (2nd August 2017) - Bruña, Sonia; González-Vadillo, Ana Mª; Ferrández, Marta; Perles, Josefina; Montero-Campillo, M. Merced; Mó, Otilia; Cuadrado, Isabel
Abstract : Two fragments resulting from the degradation of THF have been entrapped and stored in multiferrocenes. Abstract : The formation of a family of silicon- and siloxane-bridged multiferrocenyl derivatives carrying different functional groups attached to silicon, including Fc2 (CH3 )3 C(CH2 )2 SiCHCH2 (5 ), Fc2 (CH2 CH–O)SiCHCH2 (6 ), Fc2 (OH)SiCHCH2 (7 ), Fc2 (CH2 CH–O)Si–O–Si(O–CHCH2 )Fc2 (8 ) and Fc2 (CH2 CH–O)Si–O–SiFc3 (9 ) is described. Silyl vinyl ether molecules6, 8 and9 and the heteroleptic vinylsilane5 resulted from the competing metathesis reaction of lithioferrocene (FcLi), CH2 CH–OLi or (CH3 )3 C(CH2 )2 Li with the corresponding multifunctional chlorosilane, Cl3 SiCHCH2 or Cl3 Si–O–SiCl3 . The last two organolithium species have been likely formed in situ by fragmentation of the tetrahydrofuran solvent. Diferrocenylvinyloxyvinylsilane6 is noteworthy since it represents a rare example of a redox-active silyl mononomer in which two different CC polymerisable groups are directly connected to silicon. The molecular structures of the silicon-containing multiferrocenyl species5, 6, 8 and9 have been investigated by single-crystal X-ray diffraction studies, demonstrating the capture and storage processes of two ring fragments resulting from the cleavage of cyclic THF in redox-active and stable crystalline organometallic compounds. From electrochemical studies we found that by changing the anion of the supporting electrolyte from [PF6 ] − to [B(C6 F5 )4 ] −, the redox behaviour of tetrametallic disiloxane8 can be switched from a poorly resolved multistep redox process to four consecutive well-separated one-electron oxidations, corresponding to the sequential oxidation of the four ferrocenyl moieties.